PENGARUH KEPERCAYAAN DAN KEMUDAHAN AKSES TERHADAP KEPUTUSAN PEMBELIAN GEN Z DI ACCESS BY KAI SURABAYA - Shilvia Dwi Azzahra; NGAS. Dewi; I Wayan Darsana (Jurnal IPTA)
This study aims to analyze whether Trust and Ease of Access affect purchasing decisions through the Access By KAI website for Gen Z in Surabaya. The approach in this research is mixed research research. The population in this study were Gen Z users of the Access By KAI website in Surabaya with a sample of 100 users. The independent variables in this study are Trust and Ease of Access, while the dependent variable is Purchase Decision. The analysis techniques used are validity test, reliability test, classical assumption test, model accuracy test, descriptive statistical test, multiple linear regression analysis test, and hypothesis testing with the help of SPSS version 22. The results and conclusions of this study indicate that trust has an influence on increasing purchases, which means that if trust increases, the purchasing decision variable will also increase. Likewise, the ease of access variable has a significant effect on purchasing decisions, this is because that easy-to-understand and clear usage can help users increase purchases in the application. For the variables of trust and ease of access together have an effect on purchasing decisions, because both have a simultaneous influence, as evidenced by the F test worth 55,589.